Al islam and Kemuhammadiyahan (AIK) curriculum policy study - Siti Badriah; Qiqi Yuliati Zakiyah; Supiana Supiana (Educenter : Jurnal Ilmiah Pendidikan, 2023)
Muhammadiyah is an Islamic-based movement, aspiring and working to realize a truly Islamic society. AIK are special subjects at all Muhammadiyah Universities including at the Muhammadiyah University of Bandung which students must take. The AIK curriculum policy is an interesting thing to study. The purpose of this study was to elived to analyze the existing AIK curriculum policies at the Muhammadiyah University of Bandung. This study uses a qualitative research approach with analytic descriptive method. The conclusions from this study indicate that this curriculum is flexible in accordiance with conditions and changing times which are evaluated at any time in order to produce new policies that are better and in line with expectations.